Anterior decompression and plate fixation in treatment of cervical myelopathy: A multicentric retrospective review - Carlo Doria; Giulia Raffaella Mosele; Massimo Balsano; Gianluca Maestretti; Gianfilippo Caggiari (Acta Orthopaedica et Traumatologica Turcica, 2018)
Objectives: The aim of this study was to evaluate the results on anterior decompression and fusion with titanium mesh or expanding cage and plate fixation in patients with cervical myelopathy. Methods: We conducted a retrospective multicentric review of 114 patients, 75 males and 39 females, with cervical myelopathy who underwent surgical treatment between July 2009 to December 2011. All surgeries were performed via a ventral approach. Based on the type of surgery the patients received, they were divided into 3 groups: group 1 consisted of 49 patients who received multilevel corpectomies and fusion with strut iliac bone graft and plates; group 2 consisted of 26 patients who received multilevel corpectomies and fusion with titanium expanding cage and plating; group 3 consisted of 39 patients who received multilevel corpectomies and fusion using titanium mesh with autologous bone graft and anterior plating. Results: Decompression of the cervical spinal cord and grafting with plate fixation via a ventral approach demonstrated a high rate of improvement in neurological function with minimal complications. Fusion was documented radiologically in all cases. Eighty-three patients experienced a partial improvement and 41 had a complete recovery according to Nurick's myelopathy grading. Sixty-two patients were ranked as excellent, 48 as good, 4 as fair; unsatisfactory outcome was related to donor site complications. Conclusion: Spinal decompression and fusion with titanium cages and plates appears to be a safe and effective alternative in patients with cervical spinal myelopathy. Level of evidence: Level IV, therapeutic study. Keywords: Cervical, Myelopathy, Spondylosis, Corpectomy, Stenosis, Decompression, Spinal cord, Plate, Bone graft, Mesh, Cage